ONE BELT ONE ROAD (OBOR) AND THE INCREASE OF CHINA’S GLOBAL INFLUENCE - Napang, Marthen; Nurhasanah, Siti; Rohman, Syaiful (PEOPLE: International Journal of Social Sciences, 2019)
One Belt One Road (OBOR) is a development strategy proposed by Chinese leader Xi Jinping focusing on connectivity and cooperation among countries in Eurasia. OBOR revives silk road which covers strategic areas that crossing Asia, Africa, and Europe. OBOR is designed for trade purposes that can multiply trade profits with a multiplier effect. This development strategy is carried out by China as a manifestation of China’s determination to take a greater role in global development and create a trade network that will be based in China. In a global scene, OBOR is China’s real action in promoting trade, establishing unilateral liberalization, free trade agreement, and new international organization. Those actions are relevant to the principle of Liberalism. OBOR initiative was originated from the concept of Chinese Dream which was first popularized by Xi Jinping in 2013. Chinese Dream aims to rejuvenate the Chinese nation, modernization, economic prosperity, and national glory. OBOR is China’s effort to become a hegemon country, especially in Asia, generally in the world. In this research, the authors use Antonio Gramsci’s theory of hegemony and the Liberalism theory to analyse China’s efforts to realize its dreams to become a country that carries out cultural leadership that is not only superior in the economy but also in politics. The authors apply descriptive-analytical method and library research. The aims of this research are to know in what extent China’s success in embracing Eurasian countries to create a trading system that benefits both China and the countries involved, to analyse how OBOR creates economic interdependence in the region and how OBOR is used to strengthen China’s geopolitical power on a global scene.